Robustness of Water Systems in Industrial Applications. Issue 10 (10th July 2019) - Slagt, J. Marc; Henkel, Jochen
Abstract: This paper examines what makes a water treatment system robust and illustrates how to choose a system from the multitude of water treatment technologies that balances the higher costs of a more robust system with the required level of concept functionality. In this report, not all technologies can be covered, but instead the focus is on ultrafiltration, ion exchange, and reverse osmosis technology used in industrial applications and how to maximize the potential of the resulting water system by combining these technologies. Abstract : Robustness of a water treatment system is the ability to withstand change without compromising its initial stable performance. The challenge is to identify and implement a system that balances the higher costs of a more robust system with the level of functionality that operations requires. Knowledge and expertise are required to turn state‐of‐the‐art technology into state‐of‐the‐art performance.